The Dynamics of Family Harmony in Early Marriage Couples: A Qualitative Study in Ranto Panjang Village - Azijah Tussolihah Siregar; Malim Soleh Rambe; Laila Kalsum Hasibuan (Pustaka Edukasi: Jurnal Pendidikan Indonesia, 2025)
Early marriage remains a significant social phenomenon in Indonesia and has a significant impact on family dynamics. This study aims to analyze in depth the impact of early marriage on family harmony among young couples in Ranto Panjang Village, Muara Batang Gadis District. A qualitative approach using case study methods was used to understand the subjective experiences of couples who married early. Data were collected through in-depth interviews, naturalistic observations, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The results showed that early marriage was influenced by cultural factors, social pressure, and family economic conditions. The impact of early marriage is seen in emotional, psychological, social, and economic aspects, including stress, income instability, domestic conflict, and limitations in parenting and decision-making. However, family harmony can still be achieved through effective communication, extended family support, religious values, and role adaptation in the household. These findings confirm that family harmony in young couples is greatly influenced by the interaction between individual, social, and structural factors. This study makes an important contribution to efforts to prevent early marriage and strengthen families through educational interventions, counseling, and economic empowerment. Keywords: early marriage, family harmony, household dynamics, qualitative study, young couples.